Production of waste polyethylene terephthalate reinforced biocomposite with RSM design and evaluation of thermophysical properties by ANN - Aydogmus, Ercan; Arslanoglu, Hasan; Dag, Mustafa (Elsevier, 2021)
In this study, bio-unsaturated polyester (BUP) raw material is synthesized using modified palm oil (MPO). A new BUP composite has been improved by adding waste polyethylene terephthalate (WPET) to the obtained synthesis. The modified palm oil supplementation decreased the density, Shore D hardness, and elastic modulus of the BUP composite while increasing its thermal conductivity, and thermal stability. WPET filler has been used to decrease the thermal conductivity of the BUP composite, rise its elastic modulus and Shore D hardness. When parameters affecting experimental conditions are optimized using Response Surface Methodology (RSM); BUP (86 wt%), WPET (11.7 wt%), methyl ethyl ketone peroxide (MEKP: 1.6 wt%), cobalt octoate (Co. Oc: 0.7 wt%), and curing time (CT: 24 h) are approximately determined. BUP composite's density is 1324 kg/m(3), Shore D hardness 84, elastic modulus 346 MPa, thermal conductivity 0.048 W/m.K, and activation energy 135 kJ/mol. Also, when the thermophysical properties of the produced BUP composite have been evaluated using experimental data, it gives consistent results in both Artificial Neural Networks (ANN) and RSM method.
Keywords: Modified palm oil; Biocomposite; Characterization; RSM; ANN